Electrochemical Performance of Fe2O3/AB-Based Composite Electrode - Tuan Anh, Trinh; Thi Hang, Bui (VNU Journal of Science: Mathematics - Physics, 2019)
In this study, Fe 2 O 3 nanoparticles (nm) and microparticles (µm) were used as active materials and Acetylene Black carbon (AB) as an additive to prepare Fe 2 O 3 /AB composites to find a suitable material for Fe-air battery anode. The effects of grain size of iron oxide particles and additives on the electrochemical behavior of Fe 2 O 3 /AB composite electrodes in alkaline solution were investigated using cyclic voltammetry (CV), galvanostatic cycling and electrochemical impedance spectroscopy (EIS) measurements. The study results show that iron oxide nanoparticles provided better cyclability than iron oxide microparticles. The impedance of electrode increased during cycling, but the nm-Fe 2 O 3 /AB electrode gave smaller resistance than the µm-Fe 2 O 3 /AB one. The additives showed strong effects on the electrochemical behaviors of iron oxide electrodes. The AB additive enhanced the electric conductivity of Fe 2 O 3 /AB electrode and thus increased the redox reaction rate of iron oxide while K 2 S interacted with and broke down the passive layer leading to improved cyclability and giving higher capacity for Fe 2 O 3 /AB electrodes.